Argumen Adanya Tuhan: Wacana Historis dan Estetis - Mira Fauziah (Jurnal Pemikiran Islam, 2021)
Historically, humans are creatures who need God. Due to the limitations of human reason to reach the existence of God, humans perceive God in various images and different forms. Humans have built the argument for the existence of God with a historical and aesthetic approach. History proves human recognition of the existence of God as the Absolute, who creates and maintains nature and its contents. To get closer to God, humans build places of worship of God and even create God who is worshiped in the form of works of art.